2022
DOI: 10.1093/molbev/msac116
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral Sequence Reconstruction of a Cytochrome P450 Family Involved in Chemical Defense Reveals the Functional Evolution of a Promiscuous, Xenobiotic-Metabolizing Enzyme in Vertebrates

Abstract: The cytochrome P450 family 1 enzymes (CYP1s) are a diverse family of hemoprotein monooxygenases which metabolize many xenobiotics including numerous environmental carcinogens. However, their historical function and evolution remain largely unstudied. Here we investigate CYP1 evolution via the reconstruction and characterization of the vertebrate CYP1 ancestors. Younger ancestors and extant forms generally demonstrated higher activity towards typical CYP1 xenobiotic and steroid substrates than older ancestors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 84 publications
0
27
0
Order By: Relevance
“…This should make it more straightforward to determine the causative changes above the background noise of neutral drift. In our experience, a correlation is generally seen between evolutionary age and thermostability ( 110 ), so choosing ancestors that are more or less closely related should enable specific changes to be identified, by restricting the number of differences between the forms in question. However, to date, insufficient studies have been performed for the full benefit of this approach to be realized.…”
Section: The Asr Process and Factors Influencing Successmentioning
confidence: 99%
“…This should make it more straightforward to determine the causative changes above the background noise of neutral drift. In our experience, a correlation is generally seen between evolutionary age and thermostability ( 110 ), so choosing ancestors that are more or less closely related should enable specific changes to be identified, by restricting the number of differences between the forms in question. However, to date, insufficient studies have been performed for the full benefit of this approach to be realized.…”
Section: The Asr Process and Factors Influencing Successmentioning
confidence: 99%
“…Studies in the author's laboratory showed DNA shuffling could be used to develop libraries of biocatalysts with varied regioselectivity that could be mined for forms with desired properties, e.g., enhanced production of minor metabolites or novel activities (Huang et al, 2007;Johnston et al, 2007;Hunter et al, 2011;Behrendorff et al, 2013). More recently, ancestral sequence reconstruction has been applied to enhance the thermostability and solvent tolerance of drug-metabolizing P450s and to access forms with altered catalytic properties (Gumulya et al, 2018;Gumulya et al, 2019;Harris et al, 2022;Thomson et al, unpublished).…”
Section: Engineering P450 Enzymes For Dddmentioning
confidence: 99%
“…For example, ASR was used to develop more stable and robust protein scaffolds for a P450 family. 5 The ancestral enzymes, with improved thermal stability, were expressed at relatively high levels in Escherichia coli (E. coli). Another example is the analysis of an allosteric network of tryptophan synthase composed of two α and two β subunits.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This information can be used to determine which mutated residues are important in the expression of protein function or to design thermostable proteins. Although it is difficult to improve the stability of an enzyme using rational methods, ASR has been used to generate active and thermally stable proteins. For example, ASR was used to develop more stable and robust protein scaffolds for a P450 family . The ancestral enzymes, with improved thermal stability, were expressed at relatively high levels in Escherichia coli (E.…”
Section: Introductionmentioning
confidence: 99%